137-139 Hanover Street, 1855-57 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking south of 139 Hanover Street at the corner of Union Street. This multi-story brick structure houses the boot and shoe business owned by Alexander R. Wood, note the display of goods. A variety of business signs are affixed to the building, two men are standing in different doorways in the area. Written on verso Destroyed 1859 when Union Street was widened. Josiah Franklin, the father of Benjamin Franklin, was a tallon maker. 13 x 10 Photographs